Chauliodites niedzwiedzkii sp. n. (Grylloblattida: Chaulioditidae) from Triassic sediments of Poland - Aristov, Danil S.; Żyła, Dagmara; Wegierek, Piotr (Zootaxa, 2013)
A new representative of the family Chaulioditidae (Insecta, Grylloblattida), Chauliodites niedzwiedzkii sp. n., is described from the Upper Olenekian-Lower Anisian sediments of Pałęgi in Holy Cross Mountains, Poland. This is the first formal description of any fossil insect from Pałęgi area.